Analisis Usability Website Universitas Hamzanwadi terhadap Kepuasan Pengguna dengan Menggunakan User Satisfaction Model - Zaenul Amri; Muhammad Zamroni Uska; Baiq Desi Dwi Arianti (Jurnal Pendidikan Informatika (EDUMATIC), 2018)
The purpose of this study is to find out: (1) the level usability of the hamzanwadi university website for user satisfaction by using the user satisfaction model, (2) model produced by Green and Pearson 2010 with 9 variables measurement including: design credibility, content, interactivity, navigability, responsiveness, download delay, perceived usefulness, perceived ease of use, user satisfaction. This type of research is quantitative by using survey method. The population of this study is all students of Faculty of Teacher Training and Education (FKIP) Hamzanwadi University with the numbers of 3724 students and the numbers of samples in this study were 361 students using cluster sampling technique. Data collection techniques in this study using a questionnaire with likert scale. The technique used to analyze the data is descriptive statistics. The result of this study shows that (1) from 9 variable measurement of usability of website of Hamzanwadi University only 4 variables that stated good and able to fulfill user satisfaction there are, design credibility variable, content, and perceived ease of use with mean value = 11, and interactivity with value mean = 7, (2)  5 other variables are enough and have not able to meet user satisfaction there are, variable navigationability, responsiveness, download delay, perceived usefulness, and user satisfaction with mean value = 10. So it can be concluded that the overall usability of the website of Hamzanwadi University has not can meet user satisfaction.